Effects of Neighborhood’s Built Environment on Physical Activities in Gated Communities: A Review - Yasmeen Gul; Zahid Sultan; Foziah Johar (International Journal of Built Environment and Sustainability, 2016)
The emergence of gated communities throughout the world has generated significant academic interest. Several studies have been carried out that can be found in the body of literature, which have attempted to investigate the various aspects of life within the gated communities. The range of subjects studied within this context includes the types of gated communities, the associated social and governance issues, the travel patterns, and the daily physical activities. The focus of most of these studies, however, has been on the social and governance issues while a little research on the mobility pattern (i.e. walking, cycling and public transport) and physical activities in gated communities has been reported, the available literature suffers from major shortcomings such as identification of suitable indicators to investigate whether these communities have same effects on mobility patterns and physical activities as non-gated communities. The present paper, therefore, attempts to identify the methods for objective as well as subjective study of the mobility patterns and neighborhoods design which affect the physical activities through a systematic review of available literature. The paper identifies suitable indicators to investigate the rate of physical activity in gated communities. Attempt will be made to clearly chart the differences as well as similarities between the issues concerned with physical activity in gated communities and non-gated communities and attempts to introduce new objectives for future studies. The findings of this study are expected to help design an investigation into the merits or otherwise of the active living neighborhoods.